(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: a growing and broadly discussed literature has shown that the relationship between sleep duration and health is not linear. Not only are insomnia and insufficient sleep harmful to one’s health, but excessive sleep too is also not beneficial. This study tests the association between selfrated state of health and the duration and pattern of sleep: we discuss the losses and costs in terms of quality of life deriving from excessive sleep time. Methods: we use an ordered probit specification, applied to the Italian Survey on the Use of Time (sample of Italians aged fifteen and over who keep a diary for a working day). Results: we show that greater sleep duration is negatively correlated both with self-reported state of health and with self-reported health satisfaction, while respondents’ subjective perceptions of too much and too little sleep are associated with health conditions in the usual u-shaped way. Conclusions: the negative impact of long sleep on self-reported health is confirmed. However, the effect of short sleep on health conditions is positive, while a measure of decreasing sleep quality - comprising number of interruptions of sleep, insomnia and napping - is correlated to some extent with decreasing health. The public health consequences are still to be explored: the potential gains from sleep restriction are substantial, but little is known about the causal link or the risks. Further research is needed before taking policy decisions.